IMPLEMENTASI KEBIJAKAN PENYALURAN DANA DESA DI DESA MALASARI KECAMATAN CIMAUNG KABUPATEN BANDUNG - Manshur, Fahmi Fadhillah; Winangsih, Wiwin (Jurnal Sosial Politik Unla, 2023)
The problem in this study is that the distribution of Village Funds in 2022 in Desa Malasari Kecamatan Cimaung Kabupaten Bandung, in the implementation is not in accordance with what has been stipulated in Bupati Bandung Regulation Number 166 of 2021 concerning Guidelines for Village Fund Management in Kabupaten Bandung for the 2022 Fiscal Year. The purpose of the research this is to find out and analyze how the Village Fund Distribution Policy is implemented in Desa Malasari Kecamatan Cimaung Kabupaten Bandung. The theoretical approach used in this study is the factors of Policy Implementation according to Warwick in Kadji (2015: 70-72), namely: organizational capabilities, information, support, potential distribution. Based on this theoretical approach, the researcher formulated a proposition: Implementation of the Village Fund Distribution Policy in Desa Malasari Kecamatan Cimaung Kabupaten Bandung, will run optimally if it takes into account the factors of organizational capabilities, information, support and potential distribution. The research method that used is descriptive research method, with a qualitative approach, while the data obtained through literature study, participant observation, in-depth interviews and documentation. The results showed that the Village Fund Distribution Policy in Desa Malasari Kecamatan Cimaung Kabupaten Bandung, in the implementation there were supports but also obstacles. Efforts made by the Pemerintah Desa in overcoming obstacles to the implementation of the Village Fund distribution policy are by increasing coordination with the district level and activating programs related to Village Fund management policies.